2022
DOI: 10.1002/mas.21771
|View full text |Cite
|
Sign up to set email alerts
|

Methods for quantification of glycopeptides by liquid separation and mass spectrometry

Abstract: Recent advances in analytical techniques provide the opportunity to quantify even low‐abundance glycopeptides derived from complex biological mixtures, allowing for the identification of glycosylation differences between healthy samples and those derived from disease states. Herein, we discuss the sample preparation procedures and the mass spectrometry (MS) strategies that have facilitated glycopeptide quantification, as well as the standards used for glycopeptide quantification. For sample preparation, variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 189 publications
0
14
0
Order By: Relevance
“…[ 4–6 ] Likewise, protein glycosylation, one of the most typical types of PTMs, is implicated in disease hallmarks such as cancers, neurodegenerative diseases, and metabolic syndromes. [ 7–9 ] Numerous studies have demonstrated the essential roles of palmitoylation and glycosylation in the co‐regulation of critical proteins involved in certain diseases. [ 10–12 ] Recently, evidence has shown that the spike (S) or envelope (E) proteins from SARS‐CoV‐2, the causative agent of COVID‐19, can be palmitoylated and glycosylated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–6 ] Likewise, protein glycosylation, one of the most typical types of PTMs, is implicated in disease hallmarks such as cancers, neurodegenerative diseases, and metabolic syndromes. [ 7–9 ] Numerous studies have demonstrated the essential roles of palmitoylation and glycosylation in the co‐regulation of critical proteins involved in certain diseases. [ 10–12 ] Recently, evidence has shown that the spike (S) or envelope (E) proteins from SARS‐CoV‐2, the causative agent of COVID‐19, can be palmitoylated and glycosylated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Since glycosylation may greatly impact the efficacy of a drug product, the bioanalytical characterization of glycoprotein biopharmaceuticals is extremely important. To comprehensively characterize highly complex glycoproteins, novel high-performance liquid chromatography -mass spectrometry (HPLC-MS) based approaches tend towards the analysis of the protein at the different structural levels of released glycans [18][19][20], glycopeptides [21][22][23], intact protein subunits [5,24], and intact complexes [25][26][27][28][29][30], the so-called hybrid MS approaches [5,23,[31][32][33].Very recently, size exclusion high-performance liquid chromatography (SE-HPLC) hyphenated to MS was proposed as an alternative method to perform native MS in an automated fashion [34,35]. In fact, using this technique, buffer exchange of the drug products with a solution compatible with native MS can be performed directly in the HPLC system where low Mr drug additives are separated from the protein and a native mass spectrum can be acquired in an automated fashion upon direct hyphenation with MS.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the glycan compositional and structural diversity, low abundance, and macro-/microheterogeneity, protein glycosylation analysis remains challenging. During the last few decades, a variety of mass spectrometry (MS)-based methods were developed to facilitate reliable characterization and quantitation of protein and protein glycosylation analysis. …”
Section: Introductionmentioning
confidence: 99%